Association of Cord Plasma Leptin With Birth Size in Term Newborns - Wing-Kuen Tung; Shio-Jean Lin; Yea-Shwu Hwang; Ching-Ming Wu; Yun-Han Wang; Wen-Hui Tsai (Elsevier, 2009)
Leptin is secreted from adipose tissue and plays an important role in obesity. Recent studies have shown that the relationship between leptin and body fat mass may have ethnic differences. The purpose of our study was to investigate the relationship between venous umbilical cord plasma leptin and anthropometric markers in term healthy Taiwanese newborns. Methods: Umbilical venous plasma samples were obtained from 98 term neonates (48 males and 50 females) and leptin levels were analyzed by enzyme-linked immunosorbent assay. Results: Umbilical cord plasma levels of leptin were significantly higher in the female neonates than in males (p < 0.001). The large-for-gestational age and appropriate- for-gestational age newborns had significantly higher leptin cord plasma levels than the small-for-gestational age newborns (p < 0.01 and p < 0.05, respectively). In both male and female neonates, umbilical leptin levels showed significant positive correlations with birth weight and birth length. Multiple linear regression analysis revealed that birth weight was the only significant predictor of umbilical cord plasma leptin levels in both male and female neonates. However, the slopes of the regressions between leptin and birth weight in male and female neonates were not different. Conclusion: In Taiwanese healthy term neonates, leptin umbilical cord plasma levels are associated with sex and birth weight of the neonate. The relationship between leptin and birth weight may differ among different ethnic groups. These findings imply that the relationship between leptin and body fat mass may develop early in life.